Selection indices for oil content and oil yield improvement in low and high oleic acid content populations in sunflower (Helianthus annuus L.) - T. Kamalnathu1, N. Manivannan2*, R. Sasikala1 and S. Marimuthu3 (Electronic Journal of Plant Breeding, 2022)
A F2 population was partitioned into low oleic and high oleic acid content groups using a high oleic allele-specific marker. These low and high oleic acid content groups and pooled groups were subjected to variability and association analyses. The variability parameters were similar in both high oleic and low oleic populations. Traits viz., plant height, head diameter, 100-seed weight, seed yield and oil content are considered as selection indices for improving oil yield. These selection indices can be followed to improve oil yield in both high oleic and low oleic populations. However, separate selection indices to improve oil content viz., volume weight, plant height and head diameter for high oleic acid populations and volume weight, days to flowering and 100-seed weight for a low oleic populations may be followed. These results indicated that similar selection indices could not be adopted to improve a trait in all populations.